2003
DOI: 10.1002/ss.78
|View full text |Cite
|
Sign up to set email alerts
|

From First Design Brainstorm Session to Final Coat of Paint: Communication, an Essential Constant

Abstract: Hundreds of variables must be considered when undertaking even the smallest construction project. When renovating a still‐occupied seven‐hundred‐bed residence complex, however, the details to manage seem endless. Effective communication among all parties—especially students—is essential to completing the project successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Hence, on one hand we found that financial issues, sustainability, location regarding dinning and parking facilities, and proposal of common spaces are the most common factors used to make design decisions in residence halls design. Furthermore, the key finding from the design decision making point of view was that common spaces are usually proposed to enrich students' life by offering leisure, mentoring, and studying spaces (Balogh, Grimm and Hardy, 2005;Banning and Kuk, 2011;Deninger and Swift, 2009;Li, Sheely and Whalen 2005;Price 2003;Riker and Decoster 2008;Romano and Hanish 2003). On the other hand, the main issues that emerged regarding residence hall evaluations were administrative and technological issues, renovation and maintenance, special population needs, parent involvement, creation of learning communities, multicultural issues, staff issues, students' satisfaction and success, and sense of place of belonging (Amole 2009;Brandon, Hirt and Cameron, 2008;Carrol et all., 2003;Johnson and Cavins 2006;Najib, Yusof and Osman 2011;Thomsen and Eikemo 2011).…”
Section: Literature Review Of Housing Issuesmentioning
confidence: 99%
“…Hence, on one hand we found that financial issues, sustainability, location regarding dinning and parking facilities, and proposal of common spaces are the most common factors used to make design decisions in residence halls design. Furthermore, the key finding from the design decision making point of view was that common spaces are usually proposed to enrich students' life by offering leisure, mentoring, and studying spaces (Balogh, Grimm and Hardy, 2005;Banning and Kuk, 2011;Deninger and Swift, 2009;Li, Sheely and Whalen 2005;Price 2003;Riker and Decoster 2008;Romano and Hanish 2003). On the other hand, the main issues that emerged regarding residence hall evaluations were administrative and technological issues, renovation and maintenance, special population needs, parent involvement, creation of learning communities, multicultural issues, staff issues, students' satisfaction and success, and sense of place of belonging (Amole 2009;Brandon, Hirt and Cameron, 2008;Carrol et all., 2003;Johnson and Cavins 2006;Najib, Yusof and Osman 2011;Thomsen and Eikemo 2011).…”
Section: Literature Review Of Housing Issuesmentioning
confidence: 99%